Folding and stability of beta-barrel membrane proteins from Gram-negative bacteria - Pocanschi, Cosmin Lorin (My University, 2005)
Life, in the form we know it, could not be imagined without the existence of biomembranes. They are a prerequisite for the formation and functioning of cells and different organelles within the cell. Biomembranes contain phospholipids and proteins in approximately equal amounts. Although intensively studied, many questions about their organization and function remained unanswered. During their biosynthesis, many secretory and plasma membrane proteins are transported across the endoplasmic reticulum (ER) membrane in eukaryotes or across the cytoplasmic membrane in prokaryotes. How do membrane proteins insert and fold for example into the outer membrane of bacteria after translocation is largely unknown. Both classes namely alpha-helical and beta-barrel integral membrane proteins (IMPs) require either detergent micelles or lipid bilayers for folding. This thesis is focused on the folding mechanism of outer membrane proteins (OMPs) of Gram-negative bacteria that form transmembrane beta-barrels. Currently there are several studies on the folding of OMPs into detergent micelles while only the outer membrane protein A (OmpA) from Escherichia coli has been shown to quantitatively fold into lipid bilayers and has been successfully used as a model for studying the mechanism of folding of OMPs into phospholipids bilayers. The fatty core of a phospholipid bilayer requires hydrophobic amino acid residues at the interface of the integral membrane protein to the fatty acyl chains of the phospholipids. Polar amide groups of transmembrane proteins that are located in the fatty region of the membrane must form hydrogen bonds with a carbonyl oxygene of a peptide bond in close vicinity to allow the stable assembly of a protein segment in the hydrophobic region of the lipid bilayer.
This thesis describes several important advancements in the study of membrane protein folding of OMPs that will be summarized in separate paragraphs below. In the first project a new technology for isolating large amounts of beta-barrel membrane proteins was established using amphipathic polymers (amphipols). To characterize similarities and differences to OmpA folding into lipid bilayers the kinetics of OmpA folding into amphipols were studied in a second investigation. In a third study the folding kinetics of the major non-specific porin FomA of Fusobacterium nucleatum into lipid bilayers were characterized. It is shown that FomA can serve as a second, alternative model to study the folding of outer membrane proteins. Thermodynamics of folding are linked to energetics of unfolding. In a fourth investigation unfolding experiments were carried out in order to calculate the energy of folding. The ferrichrome-iron receptor FhuA from E. coli was used as an example. In the last two studies, lipid-protein interactions, that may be critical for the folding process were studied on the examples of OmpA and FhuA.
Faltung und Stabilität der beta-Fass-Aussermembranproteinen Gram-negativer Bakterien
Keywords: Protein folding; stability; outer membrane protein; 570; Proteinfaltung; Stabilität; Aussermembranprotein